Karakter Dan Pengalaman Kinerja Manajemen Konstruksi Terhadap Kualitas Suatu Proyek: Karakter Dan Pengalaman Kinerja Manajemen Konstruksi Terhadap Kualitas Suatu Proyek - Jamal (Fakultas Teknik dan Rekayasa, 2024)
The performance of construction human resources (HR) is a good or bad indicator of the production process of construction labor on a construction project. HR is an integrated ability of thinking power and physical power owned by individuals, their behavior and nature are determined by their heredity and environment, while their work performance is motivated by the desire to meet their satisfaction. This study aims to determine the relationship of character and performance experience of a construction management to project quality. The method in this research uses literature study. The results of this study indicate that the appropriate project quality begins with worker selection planning which can be seen from the character of workers such as hard workers, not intervened by circumstances, assertive, quick to make decisions, and disciplined, then the experience of workers who have often handled various project work known from the period of work, the type and number of projects undertaken, project success and other achievements,. So that worker performance can continue to improve and produce quality projects.